The Differences of Mathematics Learning Outcomes between Think Pair Share (TPS) and Number Heads Together (NHT) - Kusuma, Arie Purwa; Maskuroh, Maskuroh (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
The low learning outcomes of mathematics are not appropriate thought of learning models in the classroom. Therefore, the NHT and TPS learning models can be applied to improve the learning of outcomes of the student. This study aims to determine the differences in learning outcomes using the NHT learning model with the TPS learning model. The sampling technique is used as a random sampling cluster with 2 groups of experiments for the first experimental group  (classroom view of TPS model) and the second experimental group (classes of NHT modeling). The instrument of this research uses the test of mathematics learning result. The hypothesis test is used  T-Test. The conclusion of research that are differences in the outcomes of the two learning models (NHT and TPS) on learning outcomes, based on the marginal mean of the TPS learning model is better learning outcomes than the NHT learning model.